Evaluation of efficiency of the bioagents Trichoderma koningii and T. viride in controlling the pathogenic fungus Fusarium oxysporum f.sp. lycopersici in the pots - Norien Abdulzahra Hasan -Yehya A. Salih* ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study was conducted to know the effect of the bioagents Trichoderma koningii (T.k) and T. viride (T.v) on the pathogenic fungus Fusarium oxysporum f.sp. lycopersici the causal agent of fusarium wilt disease on tomato plant in the pots. The result of the pathogenicity test showed that F. oxysporum f.sp. lycopersici is a potential pathogenic fungus for tomato, as the percentage of germination of tomato seeds decreased to 63.3% compared to the control treatment which amounted to 86.6%. The results showed that the percentage of germination of tomato seeds reached 93%, when they treated with each of T. koningii and T. viride compared to the treatment of pathogenic fungus F. oxysporum f.sp. lycopersici, which amounted to 46%. The pots experiment revealed that T. viride and T. koningii when interacted with the pathogenic fungus F. oxysporum f.sp. lycopersici (T.v +F.o.l and T.k +F.o.l) decreased the disease severity to 17.5 and 31.4% respectively compared to the pathogenic fungus alone which amounted to 71.2%. The results also indicated that T. koningii and T. viride led to increase the plant height up to 61.6 and 60.0 cm respectively, compared to the pathogenic fungus alone which was 44.1 cm. It was observed that the bioagents T. koningii ang T. viride significantly increased the dry weight of shoot and root systems up to 74.0, 71.5, 42.5 and 43.0 gm respectively, compared to the pathogenic fungus treatment which amounted to 50.7 and 27.5 gm respectively. The results also indicated that T. viride treatment gave the highest increase in the amount of total chlorophyll which amounted to 39.6 mg.100gˉ1, followed by the treatment T.v +F.o.l, which amounted to 39.1 mg.100gˉ1, compared to the pathogenic fungus treatment, which amounted to 17.5 mg.100gˉ1. It was also noticed from the results that the interaction of each of the tow bioagents with the pathogenic fungus led to a significant increase in the height, dry weight of the shoot and root systems and the amount of total chlorophyll compared to the treatment of the pathogenic fungus alone. Finally, it was found from the total results that both of T. koningii and T. viride significantly decreased the disease severity and increased the plant growth parameters, so they have no significant differences between them.